High-bonding-strength flame-retardant composite foam board and preparation method thereof

By using epoxy foam matrix composite materials to prepare high-bonding strength flame-retardant composite foam boards, the problem of releasing highly toxic gases when using harmful foaming agents and fires during the preparation process of existing foam boards is solved, and foam boards with high heat insulation, sound insulation and environmental protection performance are achieved.

CN119858374AActive Publication Date: 2025-04-22NANJING NUOBANG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510074140.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing foam board uses harmful foaming agents during the preparation process, which leads to environmental and human health hazards, and is easily ignited during fires, releasing highly toxic gases, and has great safety hazards; at the same time, the thermal insulation performance of honeycomb sandwich panels is poor.

Method used

High bond strength flame-retardant composite foam board is prepared using epoxy foam matrix composite materials. By sandwiching the epoxy foam core between the outer skin and the inner skin, a sandwich-like whole is formed through the foaming and curing process to achieve bonding and heat insulation.

Benefits of technology

It realizes easy forming, high rigidity and good thermal insulation performance of epoxy foam-based sandwich panels, avoids the use of harmful foaming agents and adhesives, and has excellent flame retardant and environmentally friendly properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858374A_ABST
    Figure CN119858374A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to a high-bonding-strength flame-retardant composite foam board and a preparation method thereof.An epoxy foam material core is internally provided with a plurality of closed-cell small bubbles, so that the thermal radiation effect and sound conduction of an epoxy foam sandwich board are effectively prevented, and the effects of heat insulation and noise reduction are achieved; compared with a honeycomb sandwich board, the heat insulation and noise reduction performance is better, in addition, the environment-friendly flame-retardant epoxy foaming mixture used for preparing the epoxy foam-based sandwich board is good in adhesion with the inner skin and the outer skin, an adhesive does not need to be used for adhesion, a harmful solvent does not need to be added, and by casting the epoxy foaming mixture between the inner skin and the outer skin, the heat insulation performance and the noise reduction performance are better. The epoxy foam sandwich board is simple in structure, easy to form, good in rigidity and strength, good in heat insulation and noise reduction performance and excellent in environmental protection performance, can be applied to manufacturing of high-strength composite materials and has wide application prospects, and the sandwich-shaped whole body is not limited to the appearance shape of a composite body, and the sandwich-shaped whole structure is good in rigidity and strength, good in heat insulation and noise reduction performance and excellent in environmental protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a high-bonding-strength flame-retardant composite foam board and a preparation method thereof. Background Art

[0002] In the existing material field, foam boards, as commonly used heat insulation, sound insulation and filling materials, have a wide range of application scenarios. Traditional foam boards, such as polyurethane foam boards, have certain heat insulation and sound insulation properties, but they have many defects. On the one hand, the preparation process of polyurethane foam often relies on chlorofluorocarbon (CFC) foaming agents, which cause great damage to the atmospheric ozone layer. At the same time, a large amount of organic solvents and additives are required during preparation. Over time, volatile organic small molecules such as benzene and toluene in the foam continue to evaporate, causing serious harm to the environment and human health. Moreover, in the event of a fire, polyurethane rigid foam is very easy to ignite, and the combustion process releases a large amount of highly toxic gases such as hydrogen cyanide, carbon monoxide and nitric oxide. When the concentration reaches 400ppm, it can cause poisoning and death, posing a huge safety hazard.

[0003] In addition, the common sandwich panel structure is composed of a sandwich layer and inner and outer skins, the inner and outer skins are bonded to the two sides of the sandwich layer by adhesives, the sandwich layer is a honeycomb core layer or a foam core layer, the honeycomb core layer is a paper honeycomb core, an aluminum honeycomb core or a plastic honeycomb core, the foam core layer is a foam material such as polyurethane (PU) foam, phenolic foam and polystyrene foam (EPS), the sandwich layer is a honeycomb core layer is called a honeycomb sandwich panel, the sandwich layer is a foam core layer is called a foam sandwich panel, although the honeycomb sandwich panel structure has the advantages of good rigidity, high load ratio and less material use, however, due to the convection and heat radiation of the air in the honeycomb cells between the inner and outer skins, the thermal insulation performance is poor.

[0004] Patent document CN103291035A discloses a honeycomb sandwich panel. The invention bonds honeycomb aluminum and glass fiber cloth together through an adhesive to form a honeycomb sandwich panel: the upper and lower skins are bonded and fixed by an adhesive layer and a honeycomb core. However, the sandwich panel core material and the panel provided by this method are prone to peeling, affecting the mechanical properties. For example, patent document CN201510108674 discloses a honeycomb aluminum-epoxy resin composite sandwich panel and a preparation method thereof. The sandwich panel is a five-layer sandwich panel, including a pure epoxy resin protective surface layer, an epoxy resin / honeycomb aluminum composite layer, a honeycomb aluminum core layer, an epoxy resin / honeycomb aluminum composite layer and a pure epoxy resin protective surface layer. Although the sandwich panel provided by the invention has good rigidity, the sandwich panel structure has many layers, the manufacturing process is complex, the cycle is also very long, and the bonding method between the skin and the sandwich layer is not explained. In addition, patent technology document CN102198744A discloses a method for manufacturing phenolic foam-filled honeycomb core reinforced advanced composite materials, which is characterized by using open-cell phenolic impregnated honeycomb as substrate, filling foamed phenolic resin at the open hole position of the substrate and foaming to form phenolic foam-filled honeycomb core material, and then compounding the core material with phenolic fiber reinforced surface material to form phenolic foam-filled honeycomb core reinforced advanced composite materials. The advanced composite material is light in weight, heat-insulating, sound-insulating, flame-retardant and corrosion-resistant. It can be widely used in the fields of aviation, shipbuilding and rail transportation facilities manufacturing. However, the sandwich panel structure manufactured by this method has many layers, the molding process is complicated, the cost is high, and the foam expansion causes the honeycomb grid to deform and crack, which destroys the strength of the honeycomb core.

[0005] Therefore, in view of the above-mentioned related technologies, it is urgent to develop a high bonding strength flame-retardant composite foam board and a preparation method thereof. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a high bonding strength flame-retardant composite foam board and a preparation method thereof, so as to provide an epoxy foam-based sandwich panel which is easy to form, has high rigidity, and has good thermal insulation and sound insulation properties.

[0007] Based on the above purpose, the present invention provides a high-bonding strength flame-retardant composite foam board and a preparation method thereof.

[0008] A high-bonding-strength flame-retardant composite foam board, the composite foam board comprising an outer skin, an epoxy foam core and an inner skin from top to bottom;

[0009] The epoxy foam core is an epoxy foam-based composite material;

[0010] The epoxy foam-based composite material is prepared from the following raw materials: epoxy resin base material, curing agent, foaming agent, flame retardant, surfactant and toughening agent;

[0011] The epoxy resin base material is obtained by mixing bisphenol A epoxy resin and modified epoxy resin;

[0012] The modified epoxy resin is rubber modified bisphenol A epoxy resin.

[0013] Preferably, the mass ratio of the epoxy resin base material, the curing agent, the foaming agent, the flame retardant, the surfactant and the toughening agent in the epoxy foam-based composite material is 125-128:13-15:11-14:48-52:1-1.5:10-10.5.

[0014] Preferably, the mass ratio of bisphenol A epoxy resin to modified epoxy resin in the epoxy resin base material is 100-105:11.5-15.

[0015] Preferably, the curing agent is diethylenetriamine;

[0016] The blowing agent is pentane;

[0017] The flame retardant is aluminum hydroxide;

[0018] The surfactant is silicone oil;

[0019] The toughening agent is nitrile rubber.

[0020] Preferably, the thickness of the outer skin is 0.15-10 mm, and the outer skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

[0021] Preferably, the thickness of the inner skin is 0.15-10 mm, and the inner skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

[0022] Preferably, the epoxy foam core has a thickness of 3-100 mm.

[0023] Preferably, the preparation process of the modified epoxy resin is as follows:

[0024] Step A1. Place bisphenol A epoxy resin in a three-necked flask with a stirring device and a thermometer, preheat at 80° C. for 10-15 minutes to reduce the viscosity of the bisphenol A epoxy resin for subsequent mixing, then add the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin, stir at 90° C. for 3 hours at a stirring speed of 300-500 rpm, so that the carboxyl group in the carboxyl-terminated nitrile rubber fully reacts with the epoxy group in the epoxy resin to obtain a pre-modified epoxy resin;

[0025] Step A2. Add styrene-butadiene rubber particles to the pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1000-1200 rpm for 30-40 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0026] Preferably, the mass ratio of the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin in step A1 is 12-16:90-110.

[0027] Preferably, the mass ratio of the styrene-butadiene rubber particles to the pre-modified epoxy resin in step A2 is 10-13:110-120.

[0028] A method for preparing a high-bonding-strength flame-retardant composite foam board comprises the following steps:

[0029] Step S1. Preheat the bisphenol A epoxy resin and the modified epoxy resin at 35-40°C, add the flame retardant, stir at 45-50°C for 15 minutes at a stirring speed of 500-800 rpm, then add the foaming agent, stir at 800-1000 rpm for 8 minutes to obtain a mixture 1;

[0030] Step S2. Add a surfactant and a toughening agent to the mixture 1, stir at 400-700 rpm for 12 min, and finally add a curing agent, stir at 800-1200 rpm for 3 min to obtain an epoxy foam-based composite material;

[0031] Step S3. Place the inner skin and outer skin of the same height close to the mold wall and fix them vertically in the mold, the mold height is consistent with the inner skin and outer skin, and the bottom of the mold is in close contact with the inner skin and outer skin;

[0032] Step S4. Inject the epoxy foam-based composite material into a mold, place it at room temperature for 6-24 hours, and then place it at 80-120°C for 2-3 hours. After foaming and curing, demould it to obtain a high-bonding strength flame-retardant composite foam board.

[0033] Beneficial effects of the present invention:

[0034] The present invention provides a high-bonding strength flame-retardant composite foam board and a preparation method thereof, wherein the epoxy foam-based sandwich board integrates filling, potting and bonding processes. Since there are many closed-cell small bubbles inside the epoxy foam material core, the heat radiation effect and sound conduction of the epoxy foam sandwich board are effectively prevented, thereby achieving the effect of heat insulation and noise reduction. Compared with the honeycomb sandwich board, the heat insulation and noise reduction performance are better. In addition, the environmentally friendly flame-retardant epoxy foaming mixture used in the preparation of the epoxy foam-based sandwich board has good adhesion to the inner and outer skins, and no adhesive is required for bonding, and no harmful solvents are required. The epoxy foaming mixture is cast between the inner and outer skins, and a sandwich-shaped whole is formed through a single foaming and curing process, that is, the epoxy foam-based sandwich board, and is not limited to the appearance shape of the composite body.

[0035] Epoxy foam sandwich panels have simple structures, are easy to form, have good overall sandwich-shaped structural rigidity, good thermal insulation and noise reduction performance, and excellent environmental performance. They can be used in the manufacture of high-strength composite materials. Epoxy foam composite materials can not only effectively improve the strength of structural walls, but also absorb the energy of impact loads and improve the performance of structural resistance to impact damage. They have broad application prospects in the fields of naval ships, military aircraft, airplanes, buildings, and offshore structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 It is a schematic diagram of the structure of the epoxy foam core in the present invention;

[0038] Figure 2 It is a schematic diagram of the structure of the honeycomb sandwich panel in Comparative Example 1 and Comparative Example 2 of the present invention;

[0039] Figure 3 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 1 of the present invention;

[0040] Figure 4 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 2 of the present invention;

[0041] Figure 5 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 3 of the present invention;

[0042] Figure 6 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 4 of the present invention;

[0043] Figure 7This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 5 of the present invention;

[0044] Figure 8 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 6 of the present invention;

[0045] Fig. 9 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 7 of the present invention;

[0046] Fig.10 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 8 of the present invention;

[0047] Fig.11 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 9 of the present invention;

[0048] Fig.12 This is a schematic diagram of the structure of the epoxy foam sandwich panel in Example 10 of the present invention;

[0049] Fig.13 The heat and sound insulation performance test results of the samples in Example 1 and Comparative Example 1 of the present invention are as follows;

[0050] Fig.14 The test results of the thermal insulation and sound insulation performance of the samples in Example 2 and Comparative Example 2 of the present invention are as follows;

[0051] Fig.15 These are the test results of the sound pressure intensity of the samples in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0052] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0053] Embodiment 1:

[0054] Depend on Figure 3 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0055] The thickness of the outer skin is 1.5mm, and the outer skin is made of aluminum alloy;

[0056] The thickness of the epoxy foam core is 30mm;

[0057] The thickness of the inner skin is 1.5m and the inner skin is made of aluminum alloy.

[0058] Embodiment 2:

[0059] Depend on Figure 4 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0060] The thickness of the outer skin is 1.5mm, and the outer skin is a steel plate;

[0061] The thickness of the epoxy foam core is 30mm;

[0062] The thickness of the inner skin is 1.5mm and the inner skin is a steel plate.

[0063] Embodiment 3:

[0064] Depend on Figure 5 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0065] The thickness of the outer skin is 2mm, and the outer skin is made of aluminum alloy;

[0066] The thickness of the epoxy foam core is 10mm;

[0067] The thickness of the inner skin is 0.15mm, and the inner skin is a steel plate;

[0068] Embodiment 4:

[0069] Depend on Figure 6 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0070] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0071] The thickness of the epoxy foam core is 50mm;

[0072] The thickness of the inner skin is 2mm and the inner skin is made of PA66 material.

[0073] Embodiment 5:

[0074] Depend on Figure 7 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0075] The thickness of the outer skin is 3mm, and the outer skin is made of ABS material;

[0076] The thickness of the epoxy foam core is 40mm;

[0077] The thickness of the inner skin is 3mm and the inner skin is made of ABS material.

[0078] Embodiment 6:

[0079] Depend on Figure 8 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0080] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0081] The thickness of the epoxy foam core is 30mm;

[0082] The thickness of the inner skin is 2mm and the inner skin is made of ABS material.

[0083] Embodiment 7:

[0084] Depend on Fig. 9 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0085] The thickness of the outer skin is 2mm, and the outer skin is made of aluminum alloy;

[0086] The thickness of the epoxy foam core is 40mm;

[0087] The thickness of the inner skin is 3mm and the inner skin is made of PA66 material.

[0088] Embodiment 8:

[0089] Depend on Fig.10 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0090] The thickness of the outer skin is 0.2mm, and the outer skin is a carbon fiber plate;

[0091] The thickness of the epoxy foam core is 90mm;

[0092] The thickness of the inner skin is 1mm, and the inner skin is a carbon fiber plate.

[0093] Embodiment 9:

[0094] Depend on Fig.11 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0095] The thickness of the outer skin is 2mm, and the outer skin is a steel plate;

[0096] The thickness of the epoxy foam core is 100mm;

[0097] The thickness of the inner skin is 0.2mm and the inner skin is glass fiber cloth.

[0098] Embodiment 10:

[0099] Depend on Fig.12 As shown, a high bonding strength flame retardant composite foam board comprises an outer skin, an epoxy foam core and an inner skin from the outside to the inside;

[0100] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0101] The thickness of the epoxy foam core is 50mm;

[0102] The thickness of the inner skin is 5mm and the inner skin is a fiberglass plate.

[0103] Embodiment 11: A method for preparing a modified epoxy resin, comprising the following steps:

[0104] S1. 90 g of bisphenol A epoxy resin was placed in a three-necked flask with a stirring device and a thermometer, and preheated at 80° C. for 10 min to reduce the viscosity of the bisphenol A epoxy resin for subsequent mixing, and then 12 g of carboxyl-terminated nitrile rubber was added to the bisphenol A epoxy resin, and stirred at 90° C. for 3 h at a stirring speed of 300 rpm to allow the carboxyl group in the carboxyl-terminated nitrile rubber to fully react with the epoxy group in the epoxy resin to obtain a pre-modified epoxy resin;

[0105] S2. Add 10 g of styrene-butadiene rubber particles to 110 g of pre-modified epoxy resin, and mix them at room temperature using a high-speed stirrer at a stirring speed of 1000 rpm for 30 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0106] Embodiment 12: A method for preparing a modified epoxy resin, comprising the following steps:

[0107] S1. 100 g of bisphenol A epoxy resin was placed in a three-necked flask with a stirring device and a thermometer, and preheated at 80° C. for 12 min to reduce the viscosity of the bisphenol A epoxy resin for subsequent mixing, and then 14 g of carboxyl-terminated nitrile rubber was added to the bisphenol A epoxy resin, and stirred at 90° C. for 3 h at a stirring speed of 400 rpm to allow the carboxyl group in the carboxyl-terminated nitrile rubber to fully react with the epoxy group in the epoxy resin to obtain a pre-modified epoxy resin;

[0108] S2. Add 12 g of styrene-butadiene rubber particles to 115 g of pre-modified epoxy resin, and mix them at room temperature using a high-speed stirrer at a stirring speed of 1100 rpm for 35 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0109] Embodiment 13: A method for preparing a modified epoxy resin, comprising the following steps:

[0110] S1. 110 g of bisphenol A epoxy resin was placed in a three-necked flask with a stirring device and a thermometer, and preheated at 80° C. for 15 min to reduce the viscosity of the bisphenol A epoxy resin for subsequent mixing, and then 16 g of carboxyl-terminated nitrile rubber was added to the bisphenol A epoxy resin, and stirred at 90° C. for 3 h at a stirring speed of 500 rpm to allow the carboxyl group in the carboxyl-terminated nitrile rubber to fully react with the epoxy group in the epoxy resin to obtain a pre-modified epoxy resin;

[0111] S2. Add 13 g of styrene-butadiene rubber particles to 120 g of pre-modified epoxy resin, and mix them at room temperature using a high-speed stirrer at a stirring speed of 1200 rpm for 40 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0112] Example 14: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0113] S1. 100 g of bisphenol A epoxy resin and 11.5 g of the modified epoxy resin prepared in Example 11 were preheated at 35 ° C, 48 g of aluminum hydroxide was added, and stirred at 45 ° C for 15 min at a stirring speed of 500 rpm, and then 11 g of pentane was added and stirred at 800 rpm for 8 min to obtain a mixture 1;

[0114] S2 was added to the mixture 1g silicone oil and 10g nitrile rubber, stirred at 400rpm for 12min, and finally 13g diethylenetriamine was added and stirred at 800rpm for 3min to obtain an epoxy foam-based composite material;

[0115] S3. The inner skin and outer skin of the same height are placed vertically in the mold close to the mold wall and fixed, the mold height is consistent with the inner skin and outer skin, the bottom of the mold is in close contact with the inner skin and outer skin;

[0116] S4. The epoxy foam-based composite material is injected into the mold, first placed at room temperature for 8 hours, and then placed at 120°C for 1 hour. After foaming and curing, it is demoulded to obtain a high bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 500%.

[0117] Example 15: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0118] S1. 103 g of bisphenol A epoxy resin and 13 g of the modified epoxy resin prepared in Example 12 were preheated at 37 ° C, 50 g of aluminum hydroxide was added, and stirred at 47 ° C for 15 min at a stirring speed of 650 rpm, and then 12 g of pentane was added and stirred at 900 rpm for 8 min to obtain a mixture 1;

[0119] S2 was added to the mixture 1.3g silicone oil and 10.3g nitrile rubber, stirred at 550rpm for 12min, and finally 14g of diethylenetriamine was added and stirred at 1000rpm for 3min to obtain an epoxy foam-based composite material;

[0120] S3. The inner skin and outer skin of the same height are placed vertically in the mold close to the mold wall and fixed, the mold height is consistent with the inner skin and outer skin, the bottom of the mold is in close contact with the inner skin and outer skin;

[0121] S4. Inject the epoxy foam-based composite material into the mold, place it at room temperature for 24 hours, and then place it at 80°C for 3 hours. After foaming and curing, demould it to obtain a high bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 500%.

[0122] Example 16: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0123] S1. 105 g of bisphenol A epoxy resin and 15 g of the modified epoxy resin prepared in Example 13 were preheated at 40 ° C, 52 g of aluminum hydroxide was added, and stirred at 50 ° C for 15 min at a stirring speed of 800 rpm, and then 14 g of pentane was added and stirred at 1000 rpm for 8 min to obtain a mixture 1;

[0124] S2 was added to the mixture 1.5g silicone oil and 10.5g nitrile rubber, stirred at 700rpm for 12min, and finally 15g diethylenetriamine was added and stirred at 1200rpm for 3min to obtain an epoxy foam-based composite material;

[0125] S3. The inner skin and outer skin of the same height are placed vertically in the mold close to the mold wall and fixed, the mold height is consistent with the inner skin and outer skin, the bottom of the mold is in close contact with the inner skin and outer skin;

[0126] S4. The epoxy foam-based composite material is injected into the mold, first placed at room temperature for 16 hours, and then placed at 100°C for 2 hours. After foaming and curing, it is demoulded to obtain a high bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 350%.

[0127] Comparative Example 1:

[0128] Depend on Figure 2 As shown, a high bonding strength flame retardant composite foam board comprises, from outside to inside, an outer skin, a glue layer, a honeycomb core, a glue layer and an inner skin;

[0129] The thickness of the outer skin is 1.5mm, and the outer skin is made of aluminum alloy;

[0130] The thickness of the inner skin is 1.5mm, and the inner skin is made of aluminum alloy;

[0131] The height of the honeycomb core is 30 mm, and the honeycomb core is an aluminum honeycomb.

[0132] Comparative Example 2:

[0133] Depend on Figure 2 As shown, a high bonding strength flame retardant composite foam board comprises, from outside to inside, an outer skin, a glue layer, a honeycomb core, a glue layer and an inner skin;

[0134] The thickness of the outer skin is 1.5mm, and the outer skin is a steel plate;

[0135] The thickness of the inner skin is 1.5mm, and the inner skin is a steel plate;

[0136] The height of the honeycomb core is 30 mm, and the honeycomb core is an aluminum honeycomb.

[0137] from Figure 13-14 It can be seen that the faster the temperature rises, the closer the stable temperature is to the heat source temperature, the better the thermal conductivity and the worse the thermal insulation. According to the final stable temperature and the rate of temperature rise, it can be judged that: thermal conductivity: comparative example 1> comparative example 2> embodiment 2> embodiment 1; thermal insulation: embodiment 1> embodiment 2 is greater than comparative example 2> comparative example 1, indicating that the epoxy foam-based sandwich panel has good thermal insulation performance. Fig.15 It can be seen from the sound pressure intensity test results of the samples that when the sound is between 500-2000Hz, the Pq value of the sample in Example 1 is the smallest, and the Pq value of Comparative Example 1 is the largest. According to the analysis of the sound insulation performance test principle, the smaller the Pq value, the greater the sound insulation coefficient. Therefore, the thermal insulation performance can be judged: Example 1> Example 2 is greater than Comparative Example 2> Comparative Example 1, indicating that the epoxy foam-based sandwich panel has good sound insulation performance.

[0138] The high bonding strength flame-retardant composite foam board of the present invention uses high-performance flame-retardant epoxy resin as the core sandwich layer material, the outer layer is the outer skin, and the inner layer is the inner skin. The outer skin and the inner skin can be selected from one or more of metal materials such as aluminum alloy and steel plate, plastic materials such as PC, ABS, PA66, PI, PEEK and PVC, and composite materials such as glass fiber, glass fiber reinforced plastic and carbon fiber board. Through the combination of different materials, it can meet diverse usage requirements and adapt to different working conditions. The composite foam board is epoxy foam-based and has a body density of 0.15-1.00g / cm 3, composite materials with excellent flame retardant properties, which will not produce highly toxic gas hydrogen cyanide during combustion, can be safely used in crowded places to effectively protect the lives of personnel. And after testing, in the sound frequency range of 315-2000Hz, this composite foam board shows good sound insulation performance, which can effectively block external noise interference; under the same heat source, compared with honeycomb sandwich panels, its temperature is 10-25℃ lower, with excellent thermal insulation performance, which can greatly reduce heat transfer. In addition, no harmful gases and volatile harmful solvents are produced during the entire preparation process. Even if exposed to high temperature and open flame conditions, no toxic gases will be released. The environmental protection performance is outstanding, which is in line with the current green development concept. After the epoxy foaming mixture undergoes the foaming and curing process, its expansion ratio can reach 130%-500%, ensuring that the foam core layer forms an ideal closed-cell structure, giving the composite foam board excellent performance.

[0139] Comparative Example 3:

[0140] Compared with Example 14, this comparative example does not add modified epoxy resin during the preparation process of the high bonding strength flame-retardant composite foam board. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a high bonding strength flame-retardant composite foam board is obtained.

[0141] Comparative Example 4:

[0142] Compared with Example 14, this comparative example only replaces the "modified epoxy resin" with the "pre-modified epoxy resin", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high bonding strength flame-retardant composite foam board is obtained.

[0143] Comparative Example 5:

[0144] Compared with Example 14, this comparative example only replaces the "modified epoxy resin prepared in Example 11" with "an equal amount of a mixture of terminal carboxyl nitrile rubber, bisphenol A epoxy resin and styrene-butadiene rubber", and the remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a high bonding strength flame-retardant composite foam board is obtained.

[0145] Comparative Example 6:

[0146] Compared with Example 14, this comparative example only adjusts the amount of "bisphenol A epoxy resin" from "100g" to "11.5g", and adjusts the amount of "modified epoxy resin prepared in Example 11" from "11.5g" to "100g", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high bonding strength flame-retardant composite foam board is obtained.

[0147] Performance test: The following performance tests were performed on the samples prepared in Examples 14 to 16 and Comparative Examples 3 to 6. For Examples 14 to 16 and Comparative Examples 3 to 6, at least 5 samples of the same specifications were prepared for each performance test to ensure the accuracy and reliability of the data:

[0148] Bond strength test: refer to ASTM D1002-10 standard and use a universal material testing machine for testing. Cut the prepared composite foam board into specimens of specified size. The bonding surface between the outer skin of the specimen and the epoxy foam core must be flat. Use adhesive to bond the outer skin at one end of the specimen to another board of the same material to ensure that the bond is firm and free of bubbles. Stretch the specimen at a tensile rate of 5mm / min until the outer skin and the foam core are peeled off. Record the maximum tensile force displayed by the testing machine at this time. Calculate the bonding strength based on the bonding area of ​​the specimen in MPa. Before conducting the bonding strength test, the specimen needs to be visually inspected to ensure that there are no defects, impurities, or other factors that affect the test results on the bonding surface. When installing the specimen on the universal material testing machine, ensure that the specimen is evenly stressed and the stretching direction is perpendicular to the bonding surface.

[0149] Flame retardant performance test: vertical combustion test is carried out according to UL94 standard. A sample with a size of 125mm×13mm×thickness (actual thickness of composite foam board) is fixed vertically in the combustion device, and the bottom of the sample is ignited with a specified flame (methane flame, flame height is about 20mm). After burning for 10 seconds, the flame is removed, and the burning time of the sample, whether there are dripping objects, and the self-extinguishing time after the flame is extinguished are recorded. According to the standard, the flame retardant level is evaluated, which is divided into V-0, V-1, V-2, etc. V-0 is the highest flame retardant level, indicating that the total burning time of the sample does not exceed 10s after the flame is applied twice, and there is no dripping object to ignite the absorbent cotton. When testing the flame retardant performance, it must be carried out in a well-ventilated environment to ensure the safety of the test personnel. After each sample test is completed, it is necessary to wait for the combustion device to cool to room temperature before testing the next sample to avoid the influence of temperature on the test results.

[0150] Thermal insulation performance test: According to ASTM C518 standard, use the heat flow meter method. Install the composite foam board sample between the cold and hot plates of the heat flow meter device. The cold plate temperature is set to 25°C and the hot plate temperature is set to 70°C. After the temperature stabilizes, measure the heat flux density (W / m 2 ), calculate the thermal conductivity (W / m·K) according to the thickness of the sample. The lower the thermal conductivity, the better the thermal insulation performance. During the thermal insulation performance test, pay close attention to the temperature stability of the heat flow meter device to ensure that the temperature fluctuations of the cold and hot plates are within the specified range. The heat flow meter needs to be calibrated before the test to ensure the accuracy of the measurement data.

[0151] Sound insulation performance test: refer to ISO140-3 standard and use acoustic testing equipment. Make the composite foam board into a sound insulation test piece of appropriate size and install it between the sound source room and the receiving room of the sound insulation test device. The sound source room emits white noise with a frequency range of 315-2000Hz. The acoustic sensor in the receiving room measures the sound pressure level (dB) after passing through the test piece. Compare it with the sound pressure level when the test piece is not installed, and calculate the sound insulation volume (dB). The greater the sound insulation volume, the better the sound insulation performance. When testing the sound insulation performance, ensure the sealing of the sound insulation test device to prevent external noise from interfering with the test results. The acoustic sensor needs to be calibrated before and after the test to ensure the accuracy of the sound pressure level measurement.

[0152] The results are shown in Table 1 below:

[0153] Table 1

[0154]

[0155]

[0156] Data Analysis:

[0157] It can be seen from Table 1 that the high bonding strength flame-retardant composite foam board prepared by the present invention has higher bonding strength, higher flame retardancy, better heat insulation performance and sound insulation effect;

[0158] Reasons for the difference in bonding strength: In Examples 14-16, the modified epoxy resin was modified in two steps. First, carboxyl-terminated nitrile rubber (CTBN) was reacted with bisphenol A epoxy resin. The carboxyl group of CTBN was chemically bonded with the epoxy group of the epoxy resin, and a flexible segment was introduced, which increased the toughness of the epoxy resin and its adhesion to different materials. The styrene-butadiene rubber particles added later were evenly dispersed through mechanical blending, further enhancing the flexibility and stress dispersion ability of the system. This composite modification enables the epoxy resin to better fuse with the outer skin, inner skin, and foaming agent during the foaming and curing process to form a tight chemical bond and physical entanglement network; compared with Example 3, no modified epoxy resin is added, and its epoxy resin system is relatively rigid. After foaming and curing, the interface bonding with the skin only relies on the limited adhesion of the epoxy resin itself, lacking the buffering and reinforcing effect of the flexible chain segment. When subjected to tensile external force, the stress concentration phenomenon at the interface is obvious, which easily leads to peeling, resulting in low bonding strength. Comparative Example 4 uses pre-modified epoxy resin, lacks the step of further optimizing the structure of solid rubber particles, and the flexibility and stress dispersion uniformity of the system are poor. It is not as good as the embodiment, so the bonding strength is at an intermediate level, which is worse than Comparative Example 3, but not as good as Examples 14-16; Comparative Example 5 uses an equal amount of terminal carboxyl nitrile rubber, bisphenol A epoxy resin and styrene butadiene rubber mixture. Due to the lack of pre-reaction and fine blending process, the components cannot form an orderly network structure as in the embodiment, the rubber phase may agglomerate, and the role of enhancing adhesion cannot be fully exerted, resulting in unsatisfactory bonding strength; Comparative Example 6 changes the ratio of bisphenol A epoxy resin to modified epoxy resin, destroys the originally optimized formula system, makes the overall performance unbalanced, and the bonding strength is also affected. Although it is worse than Comparative Examples 3 and 5, it is not as good as the embodiment with reasonable proportions.

[0159] Reasons for the difference in flame retardant properties: The modified epoxy resins in Examples 14-16, on the one hand, CTBN itself contains a certain amount of nitrogen, which can release inert gases such as nitrogen during combustion to dilute the concentration of combustible gases and play a role in gas phase flame retardancy; on the other hand, the modification process optimizes the cross-linking structure of the epoxy resin, allowing it to form a denser and more stable carbon layer at high temperatures, blocking the transfer of heat and oxygen to the internal materials and inhibiting further combustion. Comparative Example 3 did not use modified epoxy resin. When the material was burning, the thermal stability of the epoxy resin was relatively poor, and it was easy to decompose to produce combustible small molecules. The formed carbon layer was loose and could not effectively block flames and heat, resulting in prolonged burning time and the appearance of dripping. The flame retardant grade was reduced to V-1. Comparative Example 5 was similar to Comparative Example 3. Since the optimized modified epoxy resin system was not used, the flame retardant performance was poor and only reached V-1 level. Although the overall formula of Comparative Examples 4 and 6 has been adjusted, the basic flame retardant properties of the modified epoxy resin are still retained to a certain extent, so the V-0 level can be maintained. However, some detailed indicators, such as the quality of the charcoal layer after combustion, may not be as good as Examples 14-16.

[0160] Reasons for the difference in thermal insulation performance: The higher content of modified epoxy resin in Example 16 plays a key role in the foaming process. Its optimized molecular structure makes the foamed pores more uniform, small and with a high closed-cell rate. Small and uniform pores reduce the path of heat conduction, because the heat conduction rate in gas is much lower than that in solid materials; the high closed-cell rate prevents the convective heat exchange of air, and the air is enclosed in the pores, and an effective convection cycle cannot be formed, thereby greatly reducing heat transfer. In contrast, Comparative Example 3 does not have the regulation of modified epoxy resin, and the foaming structure is relatively rough, the pore size is uneven and the closed-cell rate is low. Hot air can easily be convectively transferred through larger pores and connected pores, resulting in increased thermal conductivity and poor thermal insulation performance. Due to the adjustment of the formula, Comparative Examples 4-6 cannot accurately control the foaming process like Example 16. The pore structure is in an intermediate state, and the thermal insulation performance is also between the embodiment and Comparative Example 3.

[0161] Reasons for the difference in sound insulation performance: The modified epoxy resin system of Example 16 improves the internal microstructure of the composite foam board. On the one hand, the uniform and fine pore structure is similar to a sound-absorbing sponge. After the sound waves enter, they are reflected and scattered multiple times in the pores, and the energy is continuously consumed; on the other hand, the modified epoxy resin rich in flexible segments increases the damping properties of the material. When the sound waves cause the material to vibrate, the vibration energy can be quickly converted into other forms such as heat energy and dissipated, reducing the transmission of sound waves. Comparative Example 3 lacks the optimization of modified epoxy resin, and the pore structure is not conducive to sound absorption. The material has low damping, and sound waves are easy to penetrate, so the sound insulation is low. Comparative Examples 4-6 also have a gap in sound insulation performance because their structure is not as ideal as Example 16, and they cannot achieve the efficient sound insulation effect of Example 16.

[0162] In summary, the modified epoxy resin optimizes the microstructure, chemical bonding, material compatibility and other aspects of the composite foam board, so that Examples 14-16 show obvious advantages over Comparative Examples 3-6 in various performances, providing strong support for the high performance of high bonding strength flame-retardant composite foam boards.

[0163] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0164] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high bonding strength flame retardant composite foam board, characterized in that: The composite foam board comprises an outer skin, an epoxy foam core and an inner skin from top to bottom; The epoxy foam core is an epoxy foam-based composite material; The epoxy foam-based composite material is prepared from the following raw materials: epoxy resin base material, curing agent, foaming agent, flame retardant, surfactant and toughening agent; The epoxy resin base material is obtained by mixing bisphenol A epoxy resin and modified epoxy resin; The modified epoxy resin is rubber modified bisphenol A epoxy resin.

2. The high bonding strength flame-retardant composite foam board according to claim 1, characterized in that: The mass ratio of the epoxy resin base material, the curing agent, the foaming agent, the flame retardant, the surfactant and the toughening agent in the epoxy foam-based composite material is 125-128:13-15:11-14:48-52:1-1.5:10-10.

5.

3. The high bonding strength flame-retardant composite foam board according to claim 2, characterized in that: The mass ratio of bisphenol A epoxy resin to modified epoxy resin in the epoxy resin base material is 100-105:11.5-15.

4. The high bonding strength flame-retardant composite foam board according to claim 2, characterized in that: The curing agent is diethylenetriamine; The blowing agent is pentane; The flame retardant is aluminum hydroxide; The surfactant is silicone oil; The toughening agent is nitrile rubber.

5. The high bonding strength flame-retardant composite foam board according to claim 1, characterized in that: The thickness of the outer skin is 0.15-10 mm, and the outer skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

6. The high bonding strength flame-retardant composite foam board according to claim 1, characterized in that: The thickness of the inner skin is 0.15-10 mm, and the inner skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber; The thickness of the epoxy foam core is 3-100 mm.

7. The high bonding strength flame-retardant composite foam board according to claim 1, characterized in that: The preparation process of the modified epoxy resin is as follows: Step A1. Place bisphenol A epoxy resin in a three-necked flask with a stirring device and a thermometer, preheat at 80° C. for 10-15 minutes to reduce the viscosity of the bisphenol A epoxy resin for subsequent mixing, then add the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin, stir at 90° C. for 3 hours at a stirring speed of 300-500 rpm, so that the carboxyl group in the carboxyl-terminated nitrile rubber fully reacts with the epoxy group in the epoxy resin to obtain a pre-modified epoxy resin; Step A2. Add styrene-butadiene rubber particles to the pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1000-1200 rpm for 30-40 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

8. The high bonding strength flame-retardant composite foam board according to claim 7, characterized in that: The mass ratio of the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin in step A1 is 12-16:90-110.

9. The high bonding strength flame-retardant composite foam board according to claim 7, characterized in that: The mass ratio of the styrene-butadiene rubber particles to the pre-modified epoxy resin in step A2 is 10-13:110-120.

10. The method for preparing a high-bonding-strength flame-retardant composite foam board according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1. Preheat the bisphenol A epoxy resin and the modified epoxy resin at 35-40°C, add the flame retardant, stir at 45-50°C for 15 minutes at a stirring speed of 500-800 rpm, then add the foaming agent, stir at 800-1000 rpm for 8 minutes to obtain a mixture 1; Step S2. Add a surfactant and a toughening agent to the mixture 1, stir at 400-700 rpm for 12 min, and finally add a curing agent, stir at 800-1200 rpm for 3 min to obtain an epoxy foam-based composite material; Step S3. Place the inner skin and outer skin of the same height close to the mold wall and fix them vertically in the mold, the mold height is consistent with the inner skin and outer skin, and the bottom of the mold is in close contact with the inner skin and outer skin; Step S4. Inject the epoxy foam-based composite material into a mold, place it at room temperature for 6-24 hours, and then place it at 80-120°C for 2-3 hours. After foaming and curing, demould it to obtain a high-bonding strength flame-retardant composite foam board.

Citation Information

Patent Citations

  • Method for manufacturing phenol-formaldehyde-foam-filled honeycomb core reinforced advanced compound material

    CN102198744A

  • Honeycomb sandwich panel

    CN103291035A

  • Honeycomb aluminum-epoxy resin composite sandwich plate and preparation method thereof

    CN104760340A

  • Epoxy resin adhesive and preparation method and applications thereof

    CN102977830A

  • Stiffener film substrate composition, stiffener film substrate as well as stiffener film and steel plate composite material

    CN103509506A

Cited By

  • Production process of flame-retardant polystyrene foam board

    CN120504917A